"It really needs to be given to students" digital citizenship understanding amongst student teachers qualitative Nvivo analysis - Prasetiyo, Wibowo Heru; Naidu, Noor Banu Mahadir; Tan, Bee Piang; Sumardjoko, Bambang (Jurnal Civics: Media Kajian Kewarganegaraan, 2022)
Although the internet provides benefits, teachers' role as central figures in the learning process is imperative. Due to misuse and abuse of technology, promoting digital citizenship for student teachers was challenging. Using nine elements of digital citizenship by Mike Ribble, this study explores the knowledge and comprehension of digital citizenship (DC) among twenty student teachers involved in semi-structured interviews, observation, and documentation. The result of thematic analysis with Nvivo 12 Plus indicates that student teachers assume that DC incorporates digital literacy, the standard of behaviors, and moral guidance in an online environment. The study contributes to providing insight regarding appropriate behavior in technology use. Further studies may need to be conducted regarding teacher preparation in managing the integration of digital citizenship into the teacher education.